ENVIRONMENTAL PERFORMANCE ENCOURAGES RETURN INVESTMENT IN CONSUMPTION COMPANIES: CASE ISLAMIC STOCK INDONESIA (2016-2020) - Khoirotun Nisa, Ihda Fransiska; Rusmita, Sylva Alif; Sudaryati, Erina (Universitas Airlangga, 2022)
As khalifah (leader), human beings are supposed to guard the earth. In this modern era, one way to do it can be by supporting the companies that maintain their environmental performance. As Muslims invest in Islamic indexes, they can take care of the earth at the same time. Therefore, this study aims to examine the behavior of investors in the environmental performance of companies listed in the Islamic index. The dependent variables are stock return, and the independent are market value added (MVA), PROPER value, and return on equity (ROE). The sample of this study is consumption companies registered with Indonesia Islamic Stock Index (ISSI) from2016 to 2020. There are 90 observational data in this study. Using the multiple regression analysis techniques, this study confirms that there is a significant positive effect of the PROPER and ROE on stock returns. At the same time, the MAV has no significant positive effect on stock returns. Many other variables should be investigated further regarding their effect on stock return in consumer goodscompanies, such as NPM, ROA, and DER. Investors may consider index PROPER as the benchmark for investment in Islamic stock. There is a high potential return based on environmental performance. If the company's PROPER value is good, then there is also an indication of a high investment return.